Development of Immunochromatographic Assay for the Rapid Detection of Mycoplasma capricolum subsp. capripneumoniae Antibodies - Zhu, Zhen; Qu, Guanggang; Wang, Changjiang; Wang, Lei; Du, Jige; Li, Qianlin; Shen, Zhiqiang; Chen, Xiaoyun (Frontiers in Microbiology, 2022)
Mycoplasma capricolum subsp. capripneumoniae (Mccp) is the cause of contagious caprine pleuropneumonia (CCPP), which is a highly significant respiratory disease in goats leading to significant economic losses in Africa and Asia. Currently available procedures for the diagnosis of CCPP have some limitations in sensitivity, specificity, operation time, requirement of sophisticated equipment or skilled personnel, and cost. In this study, we developed a rapid, sensitive, and specific colloidal gold-based immunochromatographic assay (GICA) strip for the efficient on-site detection of antibodies against Mccp in the serum within 10 min. For the preparation of this colloidal GICA strip, recombinant P20 protein, the membrane protein of Mccp, was expressed by Escherichia coli prokaryotic expression system after purification was used as the binding antigen in the test. The rabbit anti-goat immunoglobulin G labeled with the colloidal gold was used as the detection probe, whereas the goat anti-rabbit immunoglobulin G was coated on the nitrocellulose membrane as the control line. The concentration of the coating antibody was optimized, and the effectiveness of this colloidal GICA strip was evaluated. Our results proved that the detection limit of the test strip was up to 1:64 dilutions for the Mccp antibody-positive serum samples with no cross-reactivity with other pathogens commonly infecting small ruminants,including goat pox virus, peste des petits ruminants virus, foot-and-mouth disease virus type A, or other mycoplasmas. Moreover, the colloidal GICA strip was more sensitive and specific than the indirect hemagglutination assay for the detection of Mccp antibodies. The 106 clinical serum samples were detected by the colloidal GICA strip compared with the complement fixation test, demonstrating an 87.74% concordance with the complement fixation test. This novel colloidal GICA strip would be an effective tool for the cost-effective and rapid diagnosis of CCPP in the field.